2017
DOI: 10.2174/1745017901713010049
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Factors of Depression, Antidepressant Use and Positive Response to Antidepressants in Perinatal and Postpartum Women

Abstract: Background:In the United States, there is a disparity in knowledge of nationwide depression prevalence, the antidepressant use and the antidepressant responses during perinatal/postpartum periods.Objective:This study investigated the predicting factors of depression, antidepressant use and positive antidepressant response during the perinatal/postpartum periods.Method:The 2007-2012 National Health and Nutrition Examination Surveys (NHANES) were combined to identify adult pregnant women, those within the 18-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…This is ascribed to the possible negative interaction between mental disorders ( e.g ., depression) and poverty, primarily because, in principle, people with depression commonly perform poorly in their daily tasks [ 32 ]. Moreover, a number of studies carried out in high-income countries revealed that people with social and economic disadvantages are more likely to develop depression [ 33 ], indicating the substantial relationships between social adversity, HIV, and depression. Based on the world federation on mental health, women tend to suffer from depression two-fold more than men due to financial issues, lack of formal education, and potential exposure to violence [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is ascribed to the possible negative interaction between mental disorders ( e.g ., depression) and poverty, primarily because, in principle, people with depression commonly perform poorly in their daily tasks [ 32 ]. Moreover, a number of studies carried out in high-income countries revealed that people with social and economic disadvantages are more likely to develop depression [ 33 ], indicating the substantial relationships between social adversity, HIV, and depression. Based on the world federation on mental health, women tend to suffer from depression two-fold more than men due to financial issues, lack of formal education, and potential exposure to violence [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depression is a clinical syndrome characterized by significant and persistent depression, speech loss, mental and motor retardation, and various physical symptoms and dysfunctions (Jiang et al, 2018). Although antidepressants can improve some mental states of depression, these drugs have more side effects, such as apathy, sleep disorders, and cognitive dysfunction (Hsiao et al, 2015;Vu and Shaya, 2017). Traditional Chinese Medicine (TCM), as a complementary and alternative medicine, has been proven to possess satisfactory effects against depression and its clinical complications.…”
Section: Highlights Introductionmentioning
confidence: 99%
“…Antidepressants, such as selective serotonin reuptake inhibitors, are the mainstay of pharmacological treatment for perinatal depression; fluvoxamine, paroxetine, and sertraline are preferred in breastfeeding women, leading to the lowest serum medication levels in infants ( Langan and Goodbred, 2016 ). According to a study conducted in the USA, about half of women diagnosed with postpartum depression are on antidepressant treatment ( Vu and Shaya, 2017 ). It is worth noting that treatment approaches for postpartum depression vary from region to region.…”
Section: Discussionmentioning
confidence: 99%